(3GdLhGgQ hGdOQQ GdeTghQIs - (3YHO GdhgGH Hf CMeO Hf Ydj GdnMnfaj, fSHg Edi eMeO GHf GdMfajI, GdTYQGfj, CHh eMeO , J (B973 (3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hHYO , abO EdJeS efi HYV GdENhGf GdNUjUjf Hi MaXge Gddg Cf CPcQ dge eG JdbjJg Yf TjNi Ydi GdNhGU HeUQ GdeMQhSI hSejJg HGdLhGgQ hGdOQQ , hhSeJ cd bhdg HGSe TF ef GdLhGgQ GdfajSI s
(3BNQgG (B:s
(3GdJUha gh Gdhbha eY GdBOGH GdTQYjI XGgQkG hHGWfkG JeJ CdaGX GdUhajI hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeO hYdi Bdg hUMHg CLeYjf hGdMeO ddg hMOg Bejf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV cdeGJgG HGdMeQI s
(3fSNI efbhdI Yf fSNI cJHJ SfI (B942 s
(3HBNQgG ELGRGJ dYOO ef GdYdeGA efge TgGH GdOjf GdaJhMi hTgGH GdOjf GdMfai hfGUQ GdOjf GddbGfi s
(3bQf GdfSN (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs